CARBONYL FORMATION IN ERYTHROCYTE MEMBRANE PROTEINS DURING AGING IN HUMANS - Jha, Rashmi; Rizvi, Syed Ibrahim (Biomedical papers, 2011)
Background: Studies have shown that oxidative stress increases with increasing human age. Protein carbonyl accumulation is an indicator of oxidative damage to proteins during aging in cells and tissues. The present study is focused on the relationship between human age and protein oxidation in erythrocyte membranes in a healthy Indian population.Materials and Methods: The sample included healthy human subjects (n = 49) between the ages of 17 to 80 years. Their blood was collected and assayed spectrophotometrically for oxidative protein damage in terms of protein carbonyls and plasma antioxidant capacity in terms of FRAP.Results: Protein carbonyl content was found to increase in an age-related pattern indicating an increase in oxidative protein damage in older subjects (p <0.0001, r = 0.8269). There was also a significant negative correlation between protein oxidation and plasma antioxidant capacity measured in terms of ferric reducing antioxidant potential (FRAP) values (p<0.0001; r = -0.8695).Conclusion: Our results substantiate the occurrence of oxidative stress during human aging. Elevated erythrocyte membrane carbonyl levels found with increasing age in this study may be viewed as a biomarker for aging.
Keywords: Aging/Protein Carbonyl/Oxidative Stress/Erythrocytes